VD_FINDINFO Jug / 2020 / 376 vom 12. Oktober 2020 - VD Tribunal cantonal (2020)
RADIATION DU RÔLE, TRANSACTION JUDICIAIRE | 109 al. 2 LPA-VD, 94 al. 1 let. c LPA-VD, 241 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)